Pelatihan Pembuatan Abon Ikan Kuwe (Charanx Ignobilis) di Desa Anyar Banten - Listiawati Listiawati; Novita Damayanti; Rizky Imam Fadillah; Muhammad Ahdan; Alma Nurul Hidayah; Vika Adha Sabillah (Batara Wisnu : Indonesian Journal of Community Services, 2022)
Anyar Village, Anyar District is a village that has local potential, namely many fishermen who often catch kuwe fish and fishermen are only used by selling their catch in the form of raw fish. The relatively cheap price is not able to provide significant benefits to the catch of kuwe fish, so innovation is needed to process it further. Seeing this situation, it is necessary to conduct training on fish kuwe into ready-to-eat foods such as shredded fish and product packaging in order to increase the selling value of fish kuwe. Making this fish floss does not require a large cost, so it is easy to be applied by kuwe fish fishermen. Meanwhile, the selling value is relatively better than the selling value of raw fish. Problems in the field in this service activity are explored through observation and interview methods. After the problems have been identified, training and socialization preparations are carried out, then training is carried out on the manufacture of shredded fish and its packaging. This activity succeeded in providing an understanding of the importance of increasing the added value of fish production through processing it into shredded fish, providing skills in making shredded fish and packaging it. Further service activities can be directed at assisting the community in obtaining P-IRT permits, selling sales through social media, and assisting the next production innovation process, among others, by trying various other flavor variants other than those tested in the current service activity